Defining the Epidemiology of Safety Risks in Neonatal Intensive Care Unit Patients Requiring Surgery. Issue 8 (December 2021) - France, Daniel J.; Slagle, Jason; Schremp, Emma; Moroz, Sarah; Hatch, L. Dupree; Grubb, Peter; Vogus, Timothy J.; Shotwell, Matthew S.; Lorinc, Amanda; Lehmann, Christoph U.; Robinson, Jamie; Crankshaw, Marlee; et al.
Abstract : Objective: The aim of the study was to determine the incidence, type, severity, preventability, and contributing factors of nonroutine events (NREs)— events perceived by care providers or skilled observers as a deviations from optimal care based on the clinical situation —in the perioperative (i.e., preoperative, operative, and postoperative) care of surgical neonates in the neonatal intensive care unit and operating room. Methods: A prospective observational study of noncardiac surgical neonates, who received preoperative and postoperative neonatal intensive care unit care, was conducted at an urban academic children's hospital between November 1, 2016, and March 31, 2018. One hundred twenty-nine surgical cases in 109 neonates were observed. The incidence and description of NREs were collected via structured researcher-administered survey tool of involved clinicians. Primary measurements included clinicians' ratings of NRE severity and contributory factors and trained research assistants' ratings of preventability. Results: One or more NREs were reported in 101 (78%) of 129 observed cases for 247 total NREs. Clinicians reported 2 (2) (median, interquartile range) NREs per NRE case with a maximum severity of 3 (1) (possible range = 1–5). Trained research assistants rated 47% of NREs as preventable and 11% as severe and preventable. The relative risks for National Surgical Quality Improvement Program – pediatric major morbidity and 30-day mortality were 1.17 (95% confidence interval = 0.92–1.48) and 1.04 (95% confidence interval = 1.00–1.08) in NRE cases versus non-NRE cases. Conclusions: The incidence of NREs in neonatal perioperative care at an academic children's hospital was high and of variable severity with a myriad of contributory factors.